2019
DOI: 10.1177/1049909119838985
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Complex Chronic Conditions: Does the Classification System Work for Infants?

Abstract: Background: One widely accepted approach to identify children with life-limiting health problems is the complex chronic conditions (CCCs) classification system. Although considered the “gold standard” for classifying children with serious illness, little is known about its performance, especially among infants. Objective/Hypothesis: This research examined the prevalence of CCCs and the infant characteristics related to a CCC classification. Methods: Multivariate regression analysis was conducted with 2012 Kids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, several studies have shown that both the 9th and the 10th revisions of ICD perform similarly in classifying children with complex chronic conditions enrolled in hospice. 32 The second limitation was that all MHBH diagnoses were coded using the ICD classification system instead of the more commonly used Diagnostic and Statistical Manual of Mental Disorders (DSM). This was the limitation of the original database, which did not include DSM codes.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that both the 9th and the 10th revisions of ICD perform similarly in classifying children with complex chronic conditions enrolled in hospice. 32 The second limitation was that all MHBH diagnoses were coded using the ICD classification system instead of the more commonly used Diagnostic and Statistical Manual of Mental Disorders (DSM). This was the limitation of the original database, which did not include DSM codes.…”
Section: Discussionmentioning
confidence: 99%
“…The study data were collected between 2011 and 2013, and all cardiac diagnoses were classified using the previous ICD-9-CM . Studies have shown, however, that both the 9th and 10th versions of the International Classification of Diseases perform similarly in classifying children with complex chronic conditions enrolled in hospice 33 . The sample was limited to children enrolled in Medicaid and did not include children with private insurance or Tricare military healthcare coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the modified CCC classification system focused on infant-specific revisions, the sampling frame was limited to infants less than 1 year of age (Lindley & Fortney, 2019). The sample was restricted to those infants who had a discharge disposition of death in the hospital occurring from January 1 to December 21, 2012.…”
Section: Methodsmentioning
confidence: 99%